Positive and negative influences of typhoons on tropospheric ozone over southern China - Z. Chen (Copernicus Publications, 2021)
Based on an ensemble of 17 typhoons that made landfall between 2014 and 2018, we investigate the positive and negative influences of typhoons on tropospheric ozone over southern China. With respect to the proximity of typhoon centres and the typhoon developmental stages, we find that surface ozone is enhanced when typhoons are 400–1500 km away during the initial stages of development (e.g. from 1 d before to 1 d after typhoon genesis). The positive ozone anomalies reach 10–20 ppbv above the background ozone level on average. The maximum enhancement of surface ozone appears at a radial distance of 1100–1300 km from the typhoon centre during these initial stages. As the typhoons approach southern China, the influences of these systems switch to reducing ozone and, hence, lead to negative ozone anomalies of 6–9 ppbv. Exploring the linkages between ozone variations and typhoon-induced meteorological evolution, we find that increasing temperature and weak winds in the atmospheric boundary layer (ABL) and dominating downward motions promote ozone production and accumulation over the outskirts of typhoons during typhoon initial stages, whereas deteriorating weather, accompanied by dropping temperature, wind gales and convective activity, reduces the production and accumulation of surface ozone when typhoons are making landfall.